The Effect of Skating on Balance and Functional Mobility of Children with Autism Disorder in Kerman - Torabi, Farnaz; Abdolkarimi Ravari, Mohadeseh; Zamankhanpour, Mahdiyeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the effects of an 8-week skating intervention on balance and functional mobility in children with ASD in Kerman, Iran.Methods and Materials: A semi-experimental pretest–posttest design with a control group was employed. Twenty children aged 7–8 years with ASD were randomly assigned to either an experimental group (n=10) or a control group (n=10). The experimental group participated in supervised skating sessions three times per week for eight weeks. Assessments included static balance (modified Stork test), dynamic balance (heel-to-toe walking test), Timed Up and Go (TUG), Six-Minute Walk Test (6MWT), and Timed Floor-to-Stand (TFTS). Measurements were taken at baseline and after the intervention. Data were analyzed using paired t-tests and ANCOVA, with a significance level set at p